Anti-dumping, intra-industry trade and quality reversals - José Luis Moraga-González; Jean-Marie Viaene (Center for Economic Studies and ifo Institute (CESifo), 2004)
We examine an export game where two firms (home and foreign), located in two different countries, produce vertically differentiated products. The foreign firm is the most efficient in terms of R&D costs of quality development and the foreign country is relatively larger and endowed with a relatively higher income. The unique (risk-dominant) Nash equilibrium involves intra-industry trade where the foreign producer manufactures a good of higher quality than the domestic firm. This equilibrium is characterized by unilateral dumping by the foreign firm into the domestic economy. Two instruments of anti-dumping (AD) policy are examined, namely, a price undertaking (PU) and an anti-dumping duty. We show that, when firms? cost asymmetries are low and countries differ substantially in size, a PU leads to a quality reversal in the international market, which gives a rationale for the domestic government to enact AD law. We also establish an equivalence result between the effects of an AD duty and a PU.
Keywords: F13; F12; 330; anti-dumping duty; intra-industry trade; price undertaking; product quality; quality reversals; Antidumping; Intraindustrieller Handel; Spieltheorie; Produktqualität; Theorie